Social and communications skills acquisition: panacea to economic safety among unemployable graduates in Nigeria (2017)
The economy of Nigeria is plagued with an alarming rate of unemployment. Stakeholders are of the view that graduates are not employable due to lack of or insufficient relevant skills Yet, there is a constant increase in the number of higher institutions of learning who produce graduates annually with the view that education guarantee employment. This proposes the appraisal of graduates from these higher education institutions of learning in Nigeria. This study, therefore, examined social and communication skills as determinants of graduate’s employability in Ibadan Metropolis, Oyo state. The study adopted the descriptive survey research design. The research was carried out in Ibadan Metropolis, Oyo state. Purposive sampling technique was used to select six local governments in Ibadan Metropolis, Oyo state. A total of 200 employers of labour were selected for the study. The results revealed employers required the employability skills (social and communication skills) (t = -10.42; df 398; p < 0.05) and (t= -5.821; df 398; p < 0.05) respectively, from graduates at high rate both private and public organizations, nevertheless graduates displayed high level of communications and social skills in Ibadan Metropolis, Oyo state. It was recommended that stakeholders should be aware of the perseverance far the creations of more job opportunities for graduates in order to tackle the problem of increasing unemployment in Nigeria